Effect of weaning age on 6-month weight of Horro lambs - Abegaz, Solomon (1991)
Effects of age at weaning on growth and mortality of 6-month-old Horro lambs, born in a 12-day period, were studied. Approximately equal group of lambs were weaned at 2,3,4,5, or 6 months of age. Growth and mortality records up to 6 months of age were take.